Are All Stroke Patients Eligible for Fast Alteplase Treatment? An Analysis of Unavoidable Delays. (20th March 2016) - Choi, Philip M. C.; Desai, Jamsheed A.; Kashyap, Devika; Stephenson, Caroline; Kamal, Noreen; Vogt, Sheldon; Bohm, Victoria; Suddes, Michael; Bugbee, Erin; Hill, Michael D.; Demchuk, Andrew M.; Smith, Eric E.
Abstract: Objectives: The National Quality Forum recently endorsed a performance measure for time to intravenous thrombolytic therapy which allows exclusions for circumstances in which fast alteplase treatment may not be possible. However, the frequency and impact of unavoidable patient reasons for long door‐to‐needle time (DNT), such as need for medical stabilization, are largely unknown in clinical practice. As part of the Hurry Acute Stroke Treatment and Evaluation‐2 (HASTE‐2) project, we sought to identify patient and systems reasons associated with longer DNT. Methods: From June 2012 to June 2013 we collected data on DNT and potential reasons for delays from 102 consecutive patients presenting directly to the emergency department who were treated with alteplase within 4.5 hours of symptom onset. Results: Mean age was 71 years, 56/113 (54%) were women, median NIH Stroke Scale score was 13, and median DNT was 53 minutes. Potential delays were noted in 59/102 (58%), of which 31/102 (31%) were unavoidable patient‐related or eligibility reasons. Median DNT was longer when patient‐related or eligibility reasons for delay were present (60 minutes) than when absent (45 minutes, p = 0.005). Multivariable modeling showed that need for urgent medical stabilization, presentation with seizure and inability to confirm eligibility were associated with 35%–50% longer DNT times. Conclusions: Up to 31% of patients have delays due to medical or eligibility‐related causes that may be legitimate reasons for providing alteplase later than the benchmark time of 60 minutes.